The Effect Of Sales Promotion, Prices, And Cash On Delivey Payment Methods On Buying Interest In The Shopee Application, A Case Study Of The Bogor Community - Lina, Lina; Pratomo, Anton Widio (Jurnal Aplikasi Bisnis Kesatuan, 2025)
The rapid progress of technology in the current era of globalization provides many important benefits for society, because it can help carry out various activities for people's lives, for example by having access to knowledge networks. Many advances and creative innovations have emerged from the presence of Intel network access, especially electronic commerce. E-Commerce is any business activity or exchange carried out using electronic media, including advertising, purchasing and payments (transactions). This research aims to determine the influence of sales promotion (X1), price (X2), and COD payment method (X3) partially and simultaneously on consumer buying interest (Y) in the Shopee application in the Bogor community. The results of this research showed that the influence of sales promotion (X1) on buying interest (Y) was obtained by a calculated t of 1.571 which was smaller than the t-table of 1.986 and a significant value of 0.120 > 0.05. So, H1 is rejected, H0 is accepted, where the second research hypothesis is accepted, which means there is no significant influence, the influence of Price (X2) on Purchase Interest (Y) is obtained by a calculated t of 5,330 which is greater than the t-table of 1.986 and a significant value of 0.000 < 0, 05. So, H2 is accepted, H0 is rejected, where the second research hypothesis is accepted, which means that there is a significant influence between Price (X2) on Purchase Intention (Y), the influence of the COD Payment Method (X3) on Purchase Intention s(Y) obtained t calculated at 0.031 smaller from the t-table 1.986 and a significant value of 0.975 > 0.05. Thus, H3 is rejected. H0 is accepted, where the second research hypothesis is accepted, which means there is no significant effect. And based on the table above, the output of the F test results shows that the significant value for the influence of X1, So it can be concluded that H3 is accepted, which means there is a simultaneous influence of X1, X2 and Simultaneously, sales promotions, prices and COD payment methods have a significant effect on purchasing interest. Keywords: Sales Promotion, Price, COD Payment Method, Purchase Interest, Shopee Application